2019
DOI: 10.1002/btpr.2938
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced functional recombinant factor IX production by human embryonic kidney cells engineered to overexpress VKORC1

Abstract: Replacement therapy with recombinant drugs is the main therapeutic strategy for hemophilia B patients. To reduce the production costs of recombinant coagulation factors, improvement of their expression and activity by enhancement of γ‐carboxylation might be of interest. The expression and functional activity of vitamin K‐dependent (VKD) coagulation proteins rely, in part, on the VKD process of γ‐carboxylation that is mediated by the enzymes γ‐carboxylase and vitamin K epoxide reductase (VKOR). Since the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…From this we speculate that the increase in γ-carboxylation leads to higher secretion efficiency and a decrease in trapped FIX in the intracellular space, indicating that the secretory machinery is affected by γ-carboxylation. It is in light of other studies that show poor secretion of FIX following γ-carboxylase overexpression (Rehemtulla et al 1993;Hallgren et al 2002;Wajih et al 2005aWajih et al , 2005b or increased secretion of FIX in overexpressed VKOR cells (Wajih et al 2005a(Wajih et al , 2005bHallgren et al 2006, Pakdaman et al 2019, implying that γ-carboxylase acts as an essential factor during protein secretion (McClure et al 1992). Moreover, it was shown that γ-carboxylation is part of the protein secretion pathway (Rishavy and Berkner 2012) and was required for both efficient secretion and anticoagulant activity (McClure et al 1992).…”
Section: Discussionsupporting
confidence: 59%
“…From this we speculate that the increase in γ-carboxylation leads to higher secretion efficiency and a decrease in trapped FIX in the intracellular space, indicating that the secretory machinery is affected by γ-carboxylation. It is in light of other studies that show poor secretion of FIX following γ-carboxylase overexpression (Rehemtulla et al 1993;Hallgren et al 2002;Wajih et al 2005aWajih et al , 2005b or increased secretion of FIX in overexpressed VKOR cells (Wajih et al 2005a(Wajih et al , 2005bHallgren et al 2006, Pakdaman et al 2019, implying that γ-carboxylase acts as an essential factor during protein secretion (McClure et al 1992). Moreover, it was shown that γ-carboxylation is part of the protein secretion pathway (Rishavy and Berkner 2012) and was required for both efficient secretion and anticoagulant activity (McClure et al 1992).…”
Section: Discussionsupporting
confidence: 59%
“…One day before transfection, 3×10 6 cells were seeded in a volume of 3 ml in 6-well plates, through which the cells were allowed to loosely adhere. The pMT-prepro-PC/FIX construct and the pCoHygro plasmid were transfected into Drosophila S2 cells employing the calcium phosphate coprecipitation method with minor modi cations [19]. After 48 h, the cells were cultured in 300 µg of hygromycin B/ml.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%